The effect of friction massage on pain intensity, PPT, and ROM in individuals with myofascial trigger points: a systematic review - Mehrdad Sadeghnia; Mehrnaz Kajbafvala; Azadeh Shadmehr (BMC Musculoskeletal Disorders)
Abstract Introduction Friction massage (FM) is a conservative treatment for managing myofascial trigger points (MTrPs). Although many studies have demonstrated the effects of FM, this manual technique significantly loads the therapist’s hands. Therefore, there is a need to evaluate FM compared to other physical therapy methods to help clinicians choose the best one. Objective This systematic review aimed to investigate the effect of FM on pain intensity, pressure pain threshold (PPT), and joint range of motion (ROM) in individuals with MTrPs. Methods PubMed/Medline, Scopus, Web of Science, Science Direct, and Google Scholar were searched from inception to 15 April 2024. All randomized control and clinical trials that assessed the effect of FM on pain intensity, PPT, and joint ROM in individuals with MTrPs were included. Results Twelve studies were included. The within-group results showed that FM could significantly improve pain intensity, PPT, and joint ROM, but compared to the control group, there was no significant superiority for improving pain intensity and PPT, and the results were inconclusive for the effect of FM on joint ROM improvement because of controversial findings. Conclusion In the short term, there is level C evidence indicating that FM may effectively reduce VAS and the PPT of MTrPs in upper trapezius. Nonetheless, high-quality and long-term research is needed to address improvements in ROM and NPRS. Due to nature of level C evidence, future well-designed RCTs should overcome the existing limitations using adequate sample sizes, long intervention periods, and long-term follow-up.